Assessing Higher Education Outcomes in Brazil - Pedrosa, Renato (International Higher Education, 2011)
Brazil is one of the few countries to have developed a full-fledged program to assess outcomes at the higher education level, for both public and private institutions. The National System of Higher Education Assessment (SINAES) was established by federal law in 2004, building upon an earlier program started in 1996, and is administered by the Ministry of Education. The system divides all programs into three groups and operates on a 3-year rotating cycle, each group of programs assessed every 3 years. It may be a good source of information and data on the problems and challenges involved, so that those interested in higher education assessment would certainly profit from taking a closer look at this interesting Brazilian experience.